MEMBERSHIP CHARACTERISTICS AND ENGAGEMENT IN AN INTERNATIONAL COMMUNITY OF PRACTICE FOR TECHNOPEDAGOGY: A QUANTITATIVE ANALYSIS: Received: 22th February 2025 Revised: 29th March 2025 Accepted: 16th June 2025 - Sabrin Housni; Gaëtan Temperman; Karim Boumazguida; Bruno De Lièvre (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This article examines the individual characteristics and motivations of members within a Community of Practice (CoP) that brings together professionals from diverse educational and geographical sectors. The CoP focuses on knowledge exchange and the development of technopedagogical skills. The study was conducted with 134 members from nine countries, featuring a predominance of female participants and substantial representation from Belgium. The research is framed within a quantitative methodological approach. It aims to understand the demographic and professional profiles of members as well as their motivations for joining the community. The findings reveal that CoP members are predominantly experienced professionals with an average age of 42 and high educational attainment, with the majority holding a university degree. Most members are actively engaged in their careers, occupying positions across a wide range of educational levels, from primary to adult continuing education. Finally, the motivations for joining the CoP are primarily related to the desire to acquire new technopedagogical skills and to interact with other professionals from diverse backgrounds. The study also highlights four main predictors of willingness to participate actively in CoP: availability of time, intention to collaborate, interest in an original and innovative learning environment, and desire to learn technopedagogical content.